Personalized Chest Computed Tomography: Minimum Diagnostic Radiation Dose Levels for the Detection of Fibrosis, Nodules, and Pneumonia - May, Matthias; Heiß, Rafael; Köhnen, Julia; Wetzl, Matthias; Wiesmüller, Marco; Treutlein, Christoph; Uder, Michael; Kopp, Markus; Bräuer, Lars (Investigative Radiology, 2022)
OBJECTIVES: The purpose of this study was to evaluate the minimum diagnostic radiation dose level for the detection of high-resolution (HR) lung structures, pulmonary nodules (PNs), and infectious diseases (IDs). MATERIALS AND METHODS: A preclinical chest computed tomography (CT) trial was performed with a human cadaver without known lung disease with incremental radiation dose using tin filter-based spectral shaping protocols. A subset of protocols for full diagnostic evaluation of HR, PN, and ID structures was translated to clinical routine. Also, a minimum diagnostic radiation dose protocol was defined (MIN). These protocols were prospectively applied over 5 months in the clinical routine under consideration of the individual clinical indication. We compared radiation dose parameters, objective and subjective image quality (IQ). RESULTS: The HR protocol was performed in 38 patients (43%), PN in 21 patients (24%), ID in 20 patients (23%), and MIN in 9 patients (10%). Radiation dose differed significantly among HR, PN, and ID (5.4, 1.2, and 0.6 mGy, respectively; P < 0.001). Differences between ID and MIN (0.2 mGy) were not significant (P = 0.262). Dose-normalized contrast-to-noise ratio was comparable among all groups (P = 0.087). Overall IQ was perfect for the HR protocol (median, 5.0) and decreased for PN (4.5), ID-CT (4.3), and MIN-CT (2.5). The delineation of disease-specific findings was high in all dedicated protocols (HR, 5.0; PN, 5.0; ID, 4.5). The MIN protocol had borderline IQ for PN and ID lesions but was insufficient for HR structures. The dose reductions were 78% (PN), 89% (ID), and 97% (MIN) compared with the HR protocols. CONCLUSIONS: Personalized chest CT tailored to the clinical indications leads to substantial dose reduction without reducing interpretability. More than 50% of patients can benefit from such individual adaptation in a clinical routine setting. Personalized radiation dose adjustments with validated diagnostic IQ are especially preferable for evaluating ID and PN lesions.
CRIS-Team Scopus Importer:2022-02-25

TIP – Training of Intensive medical support in the case of a Pandemic - Lütcke, Björn; Günther, J.; Köhnen, Julia; Puchinger, A.; Schmidt, Anita (GMS Journal for Medical Education, 2021)
The COVID-19 pandemic has led to a short-term sharp increase in the demand for auxiliary staff in emergency rooms and intensive care units. Against this background student tutors of the Medical Faculty Erlangen have developed a training concept. The aim was to familiarize students in the clinical section quickly and effectively with skills that are particularly important in a clinical assignment as (student) assistant in the care of corona patients (e.g.: personal protective equipment, intubation assistance, arterial blood collection, assessment of blood gas values and ventilation parameters). In a blended learning concept, learning materials were prepared in ad-vance and then implemented and deepened in a presence phase. The selection of learning materials and the low supervision ratio (1:2) made it possible to realize an internally differentiated approach. The offer met with great interest among students of all clinical semesters and was evaluated very positively. The skills learned can be applied widely even independently of a pandemic.
CRIS-Team Scopus Importer:2021-03-05
Keywords: COVID-19; Internal differentiation; Peer-teaching; Self-protection